Pengaruh Citra merek dan Harga Terhadap Keputusan Pembelian Mobil Wuling Almaz Pada PT. Wuling Motors Kota Kendari - Zainuddin, Muh. Zabir; M., Suyuti H.; Steven, Rendy (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2020)
This study aims to to test the influence of image of brands and prices of the decision of consumers buying the car wuling almaz he would do to PT .Wuling Motors is kendari .The research data is collected from 30 respondents who use the car wuling almaz. Respondents who obtained by using a technique the determination of a sample that is incidental sampling.A statement given by using.Questionnaires.A response by respondents of then analyzed. QuantitativeThe quantitative analysis covering test, validity and reliability the classic, assumption test the hypothesis of this test and test t, F test the coefficients determined ( r ) and multiple linear regression analysis.This research result indicates that the variable image of brands and prices simultaneously it has some positive effects and significant of the decision of the wuling almaz he would do to PT .Wuling Motors is kendari . In full variable influential brand image of the decision of a purchase with t count as much as 1,856 greater than the variable t table 1.697 while the price of influential dominant of the decision of a purchase with the value of t count as much as 1,944 , greater than t table namely 1.697 . The most dominant variable influence of the decision to buy the car in PT. Wuling almaz Wuling Motors kendari city is variable price with the regression coefficient 1,944 as much as.